The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s12967-023-04034-5
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-seq identification and clinical validation of CD138+ and circulating miR-25 in treatment response of multiple myeloma

Abstract: Background Despite significant advancements in multiple myeloma (MM) therapy, the highly heterogenous treatment response hinders reliable prognosis and tailored therapeutics. Herein, we have studied the clinical utility of miRNAs in ameliorating patients’ management. Methods miRNA-seq was performed in bone marrow CD138+ plasma cells (PCs) of 24 MM and smoldering MM (sMM) patients to analyze miRNAs profile. CD138+ and circulating miR-25 levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…This was confirmed by multivariate analysis (HR = 4.1, 95%CI = 0.79–21.32). A similar relationship was not observed for PFS [ 58 ]. The described miR-25-3p belongs to the miR-106b-25 cluster, which directly targets TP53 , inhibiting its expression, and activates the PI3K/Akt signaling pathway, inducing PTEN expression, resulting in inhibition of apoptosis and cell aging [ 59 ].…”
Section: The Role Of Mirna Expression In Diagnosis and Prognosis Of MMsupporting
confidence: 64%
“…This was confirmed by multivariate analysis (HR = 4.1, 95%CI = 0.79–21.32). A similar relationship was not observed for PFS [ 58 ]. The described miR-25-3p belongs to the miR-106b-25 cluster, which directly targets TP53 , inhibiting its expression, and activates the PI3K/Akt signaling pathway, inducing PTEN expression, resulting in inhibition of apoptosis and cell aging [ 59 ].…”
Section: The Role Of Mirna Expression In Diagnosis and Prognosis Of MMsupporting
confidence: 64%
“…Recent reports suggest that miRNA and oxidative stress programs are interconnected in many diseases, including cancer 18,19 . In line with these findings, several studies have shown dysregulated miRNA expression in myeloma cells 20–23 . Despite these reports, the molecular mechanisms underlying oxidative stress response in MM are still poorly defined; no study has examined the relationship between TAZ and miRNA or oxidative stress in MM.…”
Section: Introductionmentioning
confidence: 99%